The relationship of website quality and customer e-satisfaction in low cost carrier - Wong, Chiet Bing, 1988- author; Zainab Khalifah; Noor Hazarina Hashim, supervisor; Fakulti Pengurusan (2014)
Thesis (Sarjana Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2014